Hubungan Motivasi Kerja dengan Manajemen Waktu pada Perawat Pelaksana di Rumah Sakit ML Tahun 2025 - Lilin Meliyah; Sancka Stella G. Sihura; Ahmad Rizal (Pusat Riset dan Inovasi Nasional, 2026)
Work motivation is one of the important factors influencing time management and nurses’ performance in providing nursing care. Good time management enables nurses to complete tasks in a timely, efficient, and effective manner. This study was conducted to determine the relationship between work motivation and time management among staff nurses at ML Hospital in 2025. This research used a quantitative approach with a cross-sectional design. A total of 40 staff nurses were selected using a total sampling technique. The instruments used were questionnaires on work motivation and time management. Data were analyzed using the Spearman Rank statistical test with a significance level of < 0.05. The results showed that most respondents had good work motivation (62.5%), while the majority demonstrated a moderate level of time management (75%). The Spearman Rank test yielded a p-value of 0.005, indicating a significant relationship between work motivation and time management among staff nurses. In conclusion, there is a significant relationship between nurses’ work motivation and time management, in which higher work motivation is associated with better time management. It is recommended that hospitals enhance nurses’ motivation through managerial support and a positive work environment.